Method inventory for assessment of physical activity at VDU workplaces. - Soares, Marcelo M.; Jacobs, Karen; Ellegast, Rolf; Weber, Britta; Mahlberg, Rena (Work)
Physical inactivity and prolonged static work tasks may seriously affect health. There are numerous indications that promoting physical activity (PA) at sedentary workplaces can reduce these health risks. However, PA interventions have so far been documented rarely on the basis of medical parameters. Effects on the PA behavior are often studied only through the methods of subjective self-assessment. For this reason an extensive method inventory was developed consisting of objective PA assessment methods and various methods for documenting PA related health outcomes. The developed method inventory has been tested in a pilot intervention study at office workplaces. The current paper presents and discusses a part of the applied inventory. The methods considered here demonstrated several positive intervention effects: intervention subjects were more active, felt better, increased muscle strength and showed improvements in resting heart rate and BMI. Not all data has been analyzed to date, but the preliminary results suggest that most of the investigated methods turned out to be suitable for the documentation of intervention effects. Among the methods for which no effects were found, the question remains whether this is due to a lack of sensitivity of the method or due to aspects related to the study design.